Pullulan Acetate Nanoparticles Based Delivery System For Hydrophobic Drug - B. SANTHOSH KUMAR,; M. GANESH KUMAR,; L. SUGUNA,; T. P. SASTRY,; A. B. MANDAL, (International Journal of Pharma and Bio Sciences, 2012)
Silymarin is having antioxidant and membrane stabilizing property and acts as a defensive material in different toxic forms of liver diseases like liver cirrhosis, alcoholic liver disease. Pullulan is a good water soluble neutral linear polysaccharide consisting of α-1,6 linked maltotriose residues. It is broadly used as a food additive and is considered to be safe for human use. In the present study, silymarin was coated with pullulan acetate nanoparticles (S-PANP’S). The particle size of pullulan acetate (PA) and silymarin loaded pullulan acetate nanoparticles (S-PANP’S) was estimated by photon correlation spectroscopy and the in-vitro release of silymarin was carried out in PBS 7.4 pH; toxicity of the S-PANP’S was studied using zebra fish embryo. This study revealed that pullulan acetate might be useful as a vehicle for anti tumour drugs like silymarin.